1999
DOI: 10.1111/j.1348-0421.1999.tb02420.x
|View full text |Cite
|
Sign up to set email alerts
|

A Filamentous Phage of Vibrio parahaemolyticus O3:K6 Isolated in Laos

Abstract: The activity of the phages was inhibited by anti-Na2 pili antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Nakasone et al (15) have reported the presence of a filamentous phage (lvpf5) from a V. parahaemolyticus O3:K6 strain (LVP5) isolated in Laos. A comparison of the restriction maps of the RF and the N-terminal amino acid sequences of the major coat protein show that f237 is clearly different from lvpf5 (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakasone et al (15) have reported the presence of a filamentous phage (lvpf5) from a V. parahaemolyticus O3:K6 strain (LVP5) isolated in Laos. A comparison of the restriction maps of the RF and the N-terminal amino acid sequences of the major coat protein show that f237 is clearly different from lvpf5 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Nakasone et al (15) have reported the presence of a filamentous phage (lvpf5) from a V. parahaemolyticus O3:K6 strain (LVP5) isolated in Laos. A comparison of the restriction maps of the RF and the N-terminal amino acid sequences of the major coat protein show that f237 is clearly different from lvpf5 (15). In that study the investigators isolated lvpf5 from only a single V. parahaemolyticus O3:K6 strain (LVP5), so it is still unclear whether lvpf5 is exclusively associated with V. parahaemolyticus O3:K6 strains.…”
Section: Discussionmentioning
confidence: 99%
“…One of these was VpV 262, the genome of which has been completely sequenced (Hardies et al ., 2003). In contrast, most described VpVs are myoviruses (Muramatsu and Matsumoto, 1991;Matsuzaki et al ., 1992;Kellogg et al ., 1995), although a number of siphoviruses (Hidaka and Tokushige, 1978;Koga et al ., 1982;Koga and Kawata, 1991) and a few filamentous inoviruses (Nakanishi et al ., 1966;Taniguchi et al ., 1984;Nakasone et al ., 1999;Nasu et al ., 2000;Chang et al ., 2002) have been reported. Even though most VpV strains were siphoviruses, there was considerable variability in dimensions and genome Viruses are listed alphabetically, followed by strains isolated from oysters (LHs; Comeau et al, 2005) which were further characterized in this study.…”
Section: Vibrio Parahaemolyticus Virus Morphologies and Genome Sizesmentioning
confidence: 99%
“…A number of V. parahaemolyticus viruses (VpVs) have been isolated and characterized from the coastal waters of Japan, Laos, Hawaii, Florida, and the Pacific and Atlantic coasts of North America (Nakanishi et al ., 1966; Sklarow et al ., 1973; Baross et al ., 1974; Kellogg et al ., 1995; Nakasone et al ., 1999; Hardies et al ., 2003; Seguritan et al ., 2003; Comeau et al ., 2005). All isolates, except a few filamentous phages ( Inoviridae family), belong to the three families of tailed phages, Myoviridae , Siphoviridae and Podoviridae (Ackermann et al ., 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of the filamentous phage CTX⌽ into the bacterial genome conveys pathogenicity to V. cholerae and to Vibrio mimicus (8). Filamentous phage f237, which is similar to the previously described phage VF33, has been identified in a pandemic O3:K6 V. parahaemolyticus strain (38,39). ORF8 in this phage is unique; no homologous sequence is present in the databases, and no biological function has hitherto been identified (39).…”
mentioning
confidence: 99%